THE LANGUAGE OF MEDICINE: SOME REMARKS ON THE COMMUNICATIYE INTENTION YIOLATION - Bogusławska-Tafelska, Marta (Acta Neophilologica, 2009)
The paper constitutes a psychodynamic analysis of the language as used in the medical expertise today. Particularly, low psycholinguistic and stylistic awareness on the part of medicine practitioners is discussed, which contributes to the communication intention violation, ultimately to communication failure between the doctor and the patient being two participants in the commu- nication dyad. This preliminary discussion points to the necessity of more conscious linguistic choices on the part of people working in the health care sector, who can model their patients ‘in the direction of health’, and start prevention programs based on psycholinguistic modeling via language used in communication with the patient.